1991
DOI: 10.3109/00016359109005920
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ionic surfactants on salivary proteins adsorbed on silica surfaces

Abstract: The adsorption onto silicon oxide surfaces from water and 0.1 M acetate buffer containing 10% parotid saliva at 25 degrees C and 35 degrees C and at pH 6 was monitored in situ using ellipsometry. The silicon oxide surface was used as a model for dental enamel. The adsorption kinetics and the reversibility on rinsing were determined, and the desorbable fraction was found not to change after either 30 or 120 min of adsorption. Addition of sodium dodecyl sulfate after 30 or 120 min of saliva adsorption caused str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…After the subsequent water rinse, which may be assumed to remove mainly delmopinol bound to the surface, the remaining amount was further reduced to less than one third of its value prior to delmopinol addition. These results together with previous observations of differences in desorbability of adsorbed salivary material by buffer rinsing and elution using different types of surfactants (Arnebrant & Simonsson, 1991;Vassilakos et al, pers. comm.…”
Section: Discussionsupporting
confidence: 92%
“…After the subsequent water rinse, which may be assumed to remove mainly delmopinol bound to the surface, the remaining amount was further reduced to less than one third of its value prior to delmopinol addition. These results together with previous observations of differences in desorbability of adsorbed salivary material by buffer rinsing and elution using different types of surfactants (Arnebrant & Simonsson, 1991;Vassilakos et al, pers. comm.…”
Section: Discussionsupporting
confidence: 92%
“…At the low saliva concentrations all pellicle material was removed immediately after surfactant addition and in whole saliva the pellicle was removed after rinsing. In a recent study (Arnebrant & Simonsson, 1991) the effects of the same surfactants were studied on pellicles formed on hydrophilic surfaces from 10% parotid saliva solutions and it was noted that SDS desorbed a significant fraction, but contrary to the present study, not all the adsorbed salivary film material. The reason for this difference may be found in the composition of the samples.…”
Section: Discussionmentioning
confidence: 66%
“…Silica surfaces were used since they could be modified to either a hydrophilic or a hydrophobic character thus representing a wide range of surface properties. Ellipsometry, which was used in the present investigation, has previously been shown to be a suitable method for studies of thin films, as salivary pellicles and their interactions with surfactants (Wahlgren & Arnebrant, 1991;Arnebrant & Simonsson, 1991). In general terms the results of these studies revealed fundamental differences in the interaction of the two tested surfactants and adsorbed salivary material.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Secretion of saliva into the oral cavity occurs mainly during the consumption of foods and beverages due to mechanical and chemical stimulation via neural reflexes and is primarily secreted from three major glands [5]: parotid, submandibular and sublingual. The large mixture of amphiphilic proteins in saliva allow it to readily form adsorbed films on both hydrophobic and hydrophilic surfaces [6][7][8][9][10][11][12][13]. Oral biolubrication is considered to be primarily provided by adsorbed layers of salivary proteins such as mucin, statherin and proline-rich proteins [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%